MEMBANGUNG KEMANDIRIAN LOKAL DENGAN PENGUATAN PARTISIPASI LEMBAGA MASYARAKAT DI DESA - H. Abdul Rasul (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
The Village government is service nature front unit to society with is principal pillar for success all programs. Therefore, brace village be a necessity can not be postponed in the effort to speed up materialized society welfare as region autonomy aim.